The International Art Market Studies Association (2016)
[Dt.:] Die Vereinigung unterstützt die Studien zum internationalen Kunstmarkt. Die Website bietet Informationen zu Kongressen und nach Registrierung eine Plattform zum wissenschaftlichen Austausch über den internationalen Kunstmarkt. - [Engl.:] The purpose of this association is to support the study of art markets of all periods and geographic areas. It aims to encourage research by providing a platform for networking, gatherings and information exchange open to all.